899Stepping up: identifying small-area variation in diabetes-related lower limb amputations. (2nd September 2021) - Cramb, Doctor Susanna; Lazzarini, Doctor Peter; Barnett, Adrian; Daniel, Mark
Abstract: Background: Diabetes-related foot disease is the leading cause of lower limb amputations in Queensland. Amputations can be either minor (below the ankle joint) or major (above the ankle joint). Minor amputations may be performed to prevent major amputations prophylactically, but how these forms of amputations interrelate, and where their interrelationships are weakest and strongest, is unknown. Knowledge of small-area variation in interrelations between minor and major amputations is relevant to prevention and improved management of foot disease. Methods: Data on lower limb amputations performed between 2014 and 2018 on patients aged 20+ years with diabetes were obtained from the Queensland Hospital Admitted Patient Data Collection. Rates were calculated using the number of people, rather than the number of amputation procedures. A Bayesian hierarchical spatial multivariate model was used to examine patterns over 516 populated statistical areas 2 in Queensland. Results: During 2014 to 2018, 3, 548 Queenslanders had at least one minor amputation, and 1, 114 had at least one major amputation. Modelled amputation rates varied markedly across the State (standardised morbidity ratio (SMR) IQR: 0.67 to 1.22), with areas in far north Queensland having extremely high rates. There was consistently high area-level correlation between minor and major amputation rates. The highest SMRs for both minor and major amputations were in the Northern Peninsula. Conclusions: Elevated rates of minor and major amputations in areas in Queensland, most noticeably the far north, indicate an urgent need for greater support for people with diabetes-related foot disease. Key messages: Text: Large differences in minor and major amputation rates across Queensland indicate that certain regions require greater assistance in managing diabetes-related foot disease.